Strategi Brand Communication Dalam Menarik Minat Calon Mahasiswa Baru - Zikri Fachrul Nurhadi; Resty Mustika Pratiwi; Moh. Jafas Febrianto (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2023)
This research is motivated by the existence of competition between universities in attracting students' interest has begun to get tougher. This is coupled with private universities in Indonesia which are currently increasingly advanced and developing so that with these conditions, higher education institutions that have just been established and are not yet well known in the community feel the great impact of competition in attracting students. This will motivate every university in Indonesia to make more efforts to improve the quality and quality of the institution through the various advantages they have. The purpose of this study is to explain the brand communication strategy of FKOMINFO Garut University, seen from the four stages used, namely understanding the message, compiling persuasive messages, selecting methods and selecting media. The method used in this study uses a qualitative approach using the theory of Communication Strategy in which there are 4 aspects studied, namely understanding the message, compiling persuasive messages, choosing methods and choosing media. Data analysis techniques from this research are data reduction, data presentation, conclusion drawing and verification. Data collection techniques used are participant observation, in-depth interviews, literature study and documentation. The results of this study indicate that the communication strategy used by FKOMINFO Garut University in the aspect of understanding the message is to form a team that has been provided with information and tasks that must be carried out. Then in the aspect of compiling persuasive messages, it contains relevant information for prospective new students. Furthermore, in the aspect of method selection, namely by applying interactive and persuasive ways in delivering messages when the activity takes place. Finally, in the aspect of media selection by using various media, both conventional media and utilizing new media.